Plasma Volume to Achieve Remission in Atypical Hemolytic Uremic Syndrome - Mahdaynia, Soheila; Nakysa, Hooman; Otukesh, Hasan; Hoseini-Shamsabadi, Rozita; Nickavar, Azar (Journal of Pediatric Nephrology, 2019)
Introduction: Atypical hemolytic uremic syndrome (HUS) is defined as a heterogeneous group of disorders. Plasma infusion or plasma exchange is the rescue therapy for this life-threatening syndrome. There is no evidence for the volume of plasma required to induce remission. Materials and Methods: Between 2007 and 2018, Forty – two patients (M=20, F=22) with a diagnosis of recurrent or familial atypical hemolytic uremic syndrome (aHUS) who were admitted to Ali-Asgar Children’s Hospital were enrolled in this observational retrospective study. The total volume of plasma required for normalizing platelet (>150000) and LDH (<500 IU), eliminating hemolysis, and decreasing serum creatinine at first presentation of disease was calculated. Patients with TTP, vasculitis, and post infectious HUS were excluded. Results: The mean age of the patients was 53 months (3-144 m). The majority of patients achieved remission at first presentation by plasma infusion (5 under peritoneal dialysis and 4 under hemodialysis) but ten patients required plasmapheresis. A total of 980 units of FFP perfused with a total volume of 195.975 L. The median (range) total plasma volume required for remission was 166 ml/kg (43-2850 ml/kg). Conclusions: This study showed that the required plasma volume for the acute phase of atypical HUS for controlling the first attack of disease. Keywords: Atypical Hemolytic Uremic Syndrome; Plasma Volume; Remission Induction; Child.